Personalised Medicine and the Economy of Biotechnological Promise. Issue 1 (2nd January 2017) - Sturdy, Steve
Abstract : Rather than seek to distinguish hype from legitimate promise, it may be more helpful to think about personalised medicine as embodying a promissory economy which serves both to mobilize resources for research and — partly at least — to determine the ends to which that research is directed. Personalised medicine is a development of the larger promissory economy of medical biotechnology. As such, it systematically conflates public benefit with the pursuit of commercial and especially pharmaceutical interests. Consequently, research and development in personalised medicine tends to favour the production of expensive new treatments over unprofitable forms of prevention or more effective use of older therapies. A rebalancing of research priorities is needed to favour the pursuit of public benefit, even when it does not deliver private profits. This will in turn require sustained reflection, self-criticism and often self-denial on the part of public research funders and the scientists they support.